Application of Dual Source Mono+Combined with Cinematic Rendering in Cirrhosis Portal Vein Imaging - Xiamin LI; Xiaoying HUANG; Zhifei LI; Fangkai GUO; Pengchao WANG; Chunhui SHAN (CT Lilun yu yingyong yanjiu)
Objective: To explore the feasibility of dual-source CT virtual single-energy imaging technology (Mono+) in improving cirrhosis portal vein image quality under cinematic rendering conditions. Methods: Portal vein images of 60 patients with cirrhosis, acquired in 100/Sn 150 kVp double energy scan mode were retrospectively analyzed. Images of 40, 45, 50, 50, 55, 60, 65, 70 keV were reconstructed using Mono + technology and M-0.5 with conventional linear fusion. The CT values, signal-to-noise ratio (SNR), and contrast noise ratio (CNR) of different single-energy M-0.5 portal vein images were compared using single-factor variance analysis. Subjective image quality scores were analyzed using various rank and sum tests. Among the results of 40 keV images, the CT and CNR values of the portal, spleen, and hepatic veins were higher than those of other images, and the differences were statistically significant. Subjective scores of 40 keV, 45 keV versus those of 60 keV, 65 keV, 70 keV M-0.5, showed statistical significance. Conclusion: The dual source CT Mono+technique can improve the image quality of cirrhosis portal vein CT with cinematic rendering.